Waldemar Jochelson—a prominent ethnographer of north-eastern Siberia - Brandišauskas, Donatas (Acta Orientalia Vilnensia, 2009)
Vilnius University This article overviews the biography and ethnographic research of prominent Litvak anthropologist Waldemar Jochelson. It discusses his extensive and influential ethnographic fieldwork among indigenous people in eastern Siberia. The author of the article argues that Jochelson’s methodology, comparative research, theoretical approaches, and scientific results can have a distinctive value in history and, in particular, anthropology and ethnology studies in Lithuania.